Совершенствование системы мотивации персонала средств размещения индустрии туризма АРК - Максимюк, Н.В. (Культура народов Причерноморья, 2013)
В статье изучено понятие «мотивация персонала», рассмотрены основные теории
мотивации трудовой деятельности, даны рекомендации по совершенствованию системы мотивации
персонала средств размещения индустрии туризма АРК за счет включения показателей
удовлетворенности работой персонала, сохранения кадровой базы и пр. в систему стратегических
показателей (BSC). Для обеспечения своевременного информирования работников, системы обратной
связи, обмена идеями рекомендуется создать Веб-портал. У статті вивчене поняття «мотивація персоналу», розглянуті основні теорії мотивації
трудової діяльності, дані рекомендації з удосконалення системи мотивації персоналу засобів
розміщення індустрії туризму АРК за рахунок включення показників задоволеності роботою персоналу,
збереження кадрової бази та ін. у систему стратегічних показників (BSC). Для забезпечення
своєчасного інформування працівників, системи зворотного зв'язку, обміну ідеями рекомендується
створити Веб-портал. In the article the concept of staff motivation is studied, the basic theories of staff motivation (content
and process) are made a comparative analysis. As a result, a number of conclusions are done: 1) every theory of
staff motivation has its advantages and disadvantages, the process theory does not compete with content theory,
but rather it complement content theory; 2) the basis of an effective system of motivation is understanding
between management and its staff: in this case it is the inclusion of key perfomance indicators (KPI) of job
satisfaction of staff, maintaining human resource base, etc. in strategic indicators (Balanced Scorecard). It is
recommended to create a Web portal company to provide timely information to staff, the feedback system, the
exchange of ideas. In Web portal company it is necessary to add information about Balanced Scorecard,
successful proposals and the results of their implementation, etc. In addition it is necessary to agree the system
of bonuses to staff with Balanced Scorecard of enterprise. This will ensure the material and non-material staff
motivation, the bonuses will be predictable and fair, and the company will use the full human potential to
improve its competitiveness.